2017
DOI: 10.5811/westjem.2017.1.32180
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Study of Risky Substance Use by Injured Emergency Department Patients

Abstract: IntroductionSurvey data regarding the prevalence of risky substance use in the emergency department (ED) is not consistent. The objective of this study was to identify the prevalence of risky substance use among injured ED patients based on the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST v3.0). A secondary objective was to report on the feasibility of administering the ASSIST to this population, based on the time to conduct screening.MethodsThis cross-sectional study used screening data f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Alcohol dependence ranges from being most prevalent in A&E to least prevalent in general wards. We might have anticipated the prevalence to be higher in mental health in-patient units and A&E due to the high level of substance use comorbidity in patients with psychiatric illness and those with injuries [20,21]. This appears to be supported by the data which, despite high I 2 values, demonstrate coherent patterns of prevalence estimates across each setting.…”
Section: Discussionmentioning
confidence: 73%
“…Alcohol dependence ranges from being most prevalent in A&E to least prevalent in general wards. We might have anticipated the prevalence to be higher in mental health in-patient units and A&E due to the high level of substance use comorbidity in patients with psychiatric illness and those with injuries [20,21]. This appears to be supported by the data which, despite high I 2 values, demonstrate coherent patterns of prevalence estimates across each setting.…”
Section: Discussionmentioning
confidence: 73%
“…Similar to our study, a significant proportion of patients (33%) declined to participate in the study. Strzsak et al reported the use of a tablet-based Alcohol, Smoking and Substance Involvement Screening Test (ASSIST) to determine the prevalence of “risky substance use” in the ED [ 41 ]. Similar to our study findings, 51% screened positive for risky substance use, and the mean time to completion was 5 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…While this study included all trauma patients, data on drug and alcohol use in drivers can help inform targeted interventions. Further, injured patients have high rates of ‘risky’ drug and alcohol use [9] , [10] , [11] , which contributes to trauma recidivism [12] . Multiple professional organisations in high income countries have recommended screening and brief intervention (SBI) for substance use disorders in trauma patients [10] , [13] .…”
Section: Introductionmentioning
confidence: 99%